The Role of Parents in Language Stimulation in Children with Post-Seizure Speech Disorders - Putri Natasya Rizti (Kasyafa: Jurnal Pendidikan Agama Islam, 2025)
This study aims to explore in depth the role of parents in providing language stimulation for 5–6-year-old children experiencing post-seizure speech disorders in Siak City. Children with a history of seizures are at higher risk of neurological disruptions and oral-motor impairments that directly affect their language development. These challenges include difficulties in articulation, limited vocabulary, and slow communicative responses. This research employed a descriptive qualitative approach through in-depth interviews with parents and observations of parent–child daily interactions. The findings reveal that parents’ limited understanding of language development stages leads to inadequate and inappropriate stimulation at home. Forms of neglect such as minimal verbal interaction, low engagement in shared reading, and excessive gadget use were found to worsen speech delays. Moreover, delayed access to speech therapy causes children to miss critical developmental periods, resulting in slower recovery of language abilities. However, when parents become actively involved through oral-motor exercises, language-based play, shared reading activities, and intensive communication, noticeable improvements in speech clarity, expressive abilities, and confidence were observed. This study highlights that structured and consistent language stimulation, supported by strong collaboration among parents, teachers, and therapists, is essential for facilitating language recovery in post-seizure children. A responsive and emotionally supportive home environment serves as the foundation for effective communication development.